2014
DOI: 10.1039/c4cp00846d
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid inorganic–organic tandem solar cells for broad absorption of the solar spectrum

Abstract: We report the first hybrid tandem solar cell with solution processable active layers using colloidal PbS quantum dots (QDs) as the front subcell in combination with a polymer-fullerene rear subcell. Al/WO3 is introduced as an interlayer, yielding an open circuit voltage (VOC) equal to about 92% of the sum of the VOC of the subcells. The device exhibits a power conversion efficiency of 1.8%. Optical simulations of various tandem configurations show that combining PbS QDs with small-bandgap polymers is a promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The Author to whom correspondence should be addressed: aram.amassian@ kaust.edu.sa hybrid tandem PCE of 7.9% is one of the highest efficiencies reported to date in hybrid tandem solar cells combining CQD and organic subcells. 19,24,25 It surpasses both the efficiencies of the organic single cell (6.6%) and that of the CQD single cell (4.8%).…”
mentioning
confidence: 93%
“…The Author to whom correspondence should be addressed: aram.amassian@ kaust.edu.sa hybrid tandem PCE of 7.9% is one of the highest efficiencies reported to date in hybrid tandem solar cells combining CQD and organic subcells. 19,24,25 It surpasses both the efficiencies of the organic single cell (6.6%) and that of the CQD single cell (4.8%).…”
mentioning
confidence: 93%
“…A polymer with a narrow absorption window could provide better spectral complementarity. Speirs et al demonstrated a tandem solar cell using PbS QDs as the front subcell and P3HT:PCBM as the rear subcell [120]. As a consequence of being placed behind the PbS, the current generation in the P3HT:PCBM rear cell was still low, limiting the efficiency of this tandem to 1.8 %.…”
Section: Role Of Device Structurementioning
confidence: 97%
“…In recent years, CQD/organic hybrid tandem solar cells have been monolithically integrated and reported by several groups. [21][22][23][24][25][26] However, one noteworthy limitation in all the reports has been the unusual placement of the low bandgap CQD subcell as the front cell, namely on the transparent electrode-coated glass substrate, limiting the ability of the tandem to generate higher photocurrent. The primary reason constraining researchers to this architecture is the incompatibility of the CQD ink solvents with underlayers, including the bulk heterojunction (BHJ) organic photoactive layer and the interconnection layers (ICL).…”
Section: Toc Graphicsmentioning
confidence: 99%
“…In particular, the bottom organic active layer is easily dissolved or damaged by some of the solvents typically used for CQD coating and/or ligand exchange, imposing important restrictions on the CQD ink and its coating process. [21][22][23][24][25][26] We have set out to investigate alternative CQD ink solvents and robust ICLs which can survive the CQD coating process and provide protection for all underlayers. Octane and butlyamine are the two most commonly used solvents for conventional PbS CQD solar cells.…”
Section: Toc Graphicsmentioning
confidence: 99%